Membangun Daya Saing Investasi Indonesia: Studi Komparatif Taiwan dan Thailand dalam Sistem Ekonomi Global - Putri Hidayat, Natya Padmalalita (Department of International Relations, Brawijaya University, 2025)
This study examines the structural challenges faced by Indonesia in attracting foreign direct investment (FDI) by comparing it to investment strategies and policies in Taiwan and Thailand. This study uses a descriptive-qualitative, desk-based approach to analyze key factors such as legal certainty, human resource quality, bureaucratic efficiency, fiscal policy, infrastructure, economic digitalization, and sustainability. The results of the analysis show that Indonesia still faces significant obstacles related to legal uncertainty, overlapping regulations, low quality of human resources, inefficient bureaucracy, and inconsistencies in fiscal policy and uneven infrastructure. In addition, the inefficient environmental licensing process (AMDAL) and challenges in implementing sustainability principles are additional barriers. In contrast, Taiwan and Thailand have succeeded in improving investment competitiveness through legal reforms, strengthening education and training, digitizing the bureaucracy, fiscal incentives, developing strategic infrastructure, and integrating sustainability principles in investment policy. The research emphasizes the importance of digital transformation, strengthening the vocational education system, simplifying regulations, and increasing transparency and accountability in investment governance. By adopting a comparative approach, this study provides strategic recommendations for Indonesia to strengthen legal certainty, improve the quality of human resources, simplify bureaucracy, accelerate digital transformation, improve environmental licensing processes, and strengthen commitment to sustainable development in order to create a competitive and sustainable investment climate at the global level.